Partial response to cinacalcet treatment in a patient with secondary hyperparathyroidism undergoing hemodialysis: a case report - Conzo, Giovanni (BioMed Central, 2012)
INTRODUCTION: In the treatment of secondary hyperparathyroidism of chronic kidney disease, calcimimetics - allosteric modulators of the calcium-sensing receptor - inhibit glandular hyperplasia and significantly reduce circulating parathyroid hormone levels. They have a major impact on the management of secondary hyperparathyroidism. CASE PRESENTATION: We present the clinical case of a 41-year-old Caucasian man undergoing chronic hemodialysis, who had a parathyroidectomy to treat severe secondary hyperparathyroidism resistant to cinacalcet treatment. Preoperatively, 24 months after high-dose cinacalcet hydrochloride, we observed a persistently elevated intact parathyroid hormone serum level, and detected clear parathyroid gland hyperplasia regression on ultrasound. We performed a three-gland parathyroidectomy, which was assumed to be total, associated with a hemithyroidectomy. Our patient then entered a hypoparathyroid state. A histopathological examination showed that the removed parathyroid glands were of small size, with a total weight of 1g, associated with a multifocal small papillary thyroid cancer. CONCLUSION: In the management of secondary hyperparathyroidism, cinacalcet hydrochloride effectively reduces total parathyroid gland hyperplasia. However, a persisting elevated intact parathyroid hormone serum level may be observed, demonstrating that reduced parathyroid hyperplastic tissue may still be associated with severe secondary hyperparathyroidism. Even if calcimimetics are very effective in secondary hyperparathyroidism treatment, further studies are necessary for a better understanding of their actions.